An Approach for Securing JSON Objects through Chaotic Synchronization - Gómez Omar S.; Rosero Raúl H.; Estrada-Gutiérrez Juan C.; Jiménez-Rodríguez Maricela (Cybernetics and Information Technologies, 2022)
Nowadays the interoperability of web applications is carried out by the use of data exchange formats such as XML and JavaScript Object Notation (JSON). Due to its simplicity, JSON objects are the most common way for sending information over the HTTP protocol. With the aim of adding a security mechanism to JSON objects, in this work we propose an encryption approach for cipher JSON objects through the use of chaotic synchronization. Synchronization ability between two chaotic systems offers the possibility of securing information between two points. Our approach includes mechanisms for diffusing and confusing JSON objects (plaintext), which yields a proper ciphertext. Our approach can be applied as an alternative to the existing securing JSON approaches such as JSON Web Encryption (JWE).